Potential effect of the non-neuronal cardiac cholinergic system on hepatic glucose and energy metabolism - Kurabayashi, Atsushi; Iwashita, Waka; Furihata, Kaoru; Fukuhara, Hideo; Inoue, Keiji (Frontiers in Cardiovascular Medicine, 2024)
The vagus nerve belongs to the parasympathetic nervous system, which is involved in the regulation of organs throughout the body. Since the discovery of the non-neuronal cardiac cholinergic system (NNCCS), several studies have provided evidence for the positive role of acetylcholine (ACh) released from cardiomyocytes against cardiovascular diseases, such as sympathetic hyperreactivityinduced cardiac remodeling and dysfunction as well as myocardial infarction. Non-neuronal ACh released from cardiomyocytes is believed to regulate key physiological functions of the heart, such as attenuating heart rate, offsetting hypertrophic signals, maintaining action potential propagation, and modulating cardiac energy metabolism through the muscarinic ACh receptor in an auto/paracrine manner. Moreover, the NNCCS may also affect peripheral remote organs (e.g., liver) through the vagus nerve. Remote ischemic preconditioning (RIPC) and NNCCS activate the central nervous system and afferent vagus nerve. RIPC affects hepatic glucose and energy metabolism through the central nervous system and vagus nerve. In this review, we discuss the mechanisms and potential factors responsible for NNCCS in glucose and energy metabolism in the liver.